High-fat liquid Lieber-DeCarli diet for an animal model of nonalcoholic steatohepatitis: does it really work? - ÇELİKEL, ÇİĞDEM (SPRINGER, 2007)
We could not reproduce the model described by Lieber et al for nonalcoholic steatohepatitis model in rats. In our trial the high fat liquid diet group of rats gained nearly 100 g or less weight compared to the mean weight gain stated in the original article. However, the fasting glucose level was statistically higher in this group as compared to the chow diet group. Some pathological abnormalities in the duodenum and jejunum samples were observed in the high fat liquid diet group. We do not know the exact reason for these changes. Overall, our study results arose some suspicions about the reproducibility of the model. Furthermore, to the best of our knowledge, no study using the proposed model has been published so far.
Keywords: high-fat liquid diet; Lieber-DeCarli diet; nonalcoholic steatohepatitis; animal model; ENERGY-INTAKE; RATS; EXPENDITURE; OBESITY